2015
DOI: 10.1155/2015/352487
|View full text |Cite|
|
Sign up to set email alerts
|

Strategy for the Management of Diabetic Macular Edema: The European Vitreo-Retinal Society Macular Edema Study

Abstract: Objective. To compare the efficacy of different therapies in the treatment of diabetic macular edema (DME). Design. Nonrandomized, multicenter clinical study. Participants. 86 retina specialists from 29 countries provided clinical information on 2,603 patients with macular edema including 870 patients with DME. Methods. Reported data included the type and number of treatment(s) performed, the pre- and posttreatment visual acuities, and other clinical findings. The results were analyzed by the French INSEE (Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 49 publications
(45 reference statements)
1
29
0
4
Order By: Relevance
“…5 Meanwhile, other surgeonsreserve scleral buckling only for second intervention. 3 In this study, we found that retinal re-attachment was successful with combine PPV with encircling buckle in 4/7 eyes (57%) and PPV alone was 42% (8/19 eyes). Ambresin et al, reported the success rate of management of GRT with vitrectomy, internal tamponade, and peripheral 360 degrees photocoagulation of the retina without scleral buckle is high (94.4%).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…5 Meanwhile, other surgeonsreserve scleral buckling only for second intervention. 3 In this study, we found that retinal re-attachment was successful with combine PPV with encircling buckle in 4/7 eyes (57%) and PPV alone was 42% (8/19 eyes). Ambresin et al, reported the success rate of management of GRT with vitrectomy, internal tamponade, and peripheral 360 degrees photocoagulation of the retina without scleral buckle is high (94.4%).…”
Section: Discussionmentioning
confidence: 54%
“…3,12 However this procedure has also been implicated in complicating the closure of GRT due to distortion of the shape of the eye, fish-mouthing and tendency to increase 'slippage' of the retina posteriorly and the possible induction of PVR due to additional trauma. 3,8 Conversely, other surgeons prefer adjunctive buckling in as a primary procedure aiming to reduce the failure rate. Their rationale was that scleral buckling reduces the early and late tractional forces and supports areas of un-detected retinal breaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the superiority of ILM peeling over other therapies for DMO has been suggested by a non-randomised study. 6 If future trials of intravitreal therapies for DMO are contemplated, one arm of the study should comprise vitrectomy and ILM peeling. The review is an excellent summary of all literature on this interesting topic; nevertheless, one of the largest surgical case series is missing.…”
Section: Sir Treatment Trials For Diabetic Macular Oedemamentioning
confidence: 99%
“…Recently, the superiority of ILM peeling over other therapies for DMO has been suggested by a non-randomised study. 6 If future trials of intravitreal therapies for DMO are contemplated, one arm of the study should comprise vitrectomy and ILM peeling.…”
mentioning
confidence: 99%